(untitled) (Jurnal Ilmiah Psikologi MIND SET, 2025)
Having children is considered necessary in a marriage, even though not all couples are fortunate enough to be blessed with children, which can impact their marital flourishing. This research aims to see the differences in marital flourishing between married individuals who are childless and married individuals who are blessed with one child and two children. There were 189 respondents, 17 men and 172 women, young adults (21-40 years old) that spread across Java, obtained through purposive sampling techniques. The questionnaire used is the Relationship Flourishing Scale. Based on the Mann Whitney-U, there is a difference in marital flourishing between married individuals who are childless and individuals who have one child with Sig. (2 tailed) 0.008 (p<0.05); meanwhile, there was no difference between married individuals who are childless and individuals with two children with Sig. (2 tailed) 0.080 (p>0.05). The mean score for the group of married individuals yet childless is higher than (52,56) that of individuals who have one (47,97) and two children (49,40). It concluded that being childless does not equal low-quality marriage or not having marital flourishing. Professionals can design interventions to increase marital flourishing in individuals with children.